Implementation of Roll-on Roll-off Shipping Program Davao, Philippines – Bitung, Indonesia - Mamentu, Michael (Journal La Sociale, 2024)
In April 2017, President Jokowi and Philippine President Rodrigo Duterte agreed to open a trade cruise between General Santos Davao and Bitung, North Sulawesi. The goal is not only to strengthen relations between fellow ASEAN member countries, but also to realize the ASEAN Economic Community agreement in a more concrete form. This deal was later named "Roll-On Roll-Off (RORO) shipping. However, this Roll-On Roll-Off cruise only runs once. The Super Shuttle RoRo ship from Davao carrying 5 containers of various Philippine products arrived and returned from Bitung Port without carrying any goods. In 2019, President Jokowi ordered that the General Santos/Davao – Bitung Roll-On Roll-Off cruise be reactivated. However, many things must be fixed so that the goals of this agreement can be achieved. Therefore, on the basis of this fact, this study seeks to find all the instrumental weaknesses of the implementation of this program. The ultimate goal is to provide recommendations for the right program design so that the Roll-On Roll Off Cruise can provide results in accordance with what is expected by the Governments of both countries.